Respuesta :

-3x + y = 4

Solve for y

y = 3x + 4

Plug this y value into the other equation.

-9x + 5y = -1

-9x + 5(3x + 4) = -1

Distribute 5(3x + 4)

-9x + 15x + 20 = -1

Subtract 20 from both sides

-9x + 15x + 20 - 20 = -1 - 20

-9x + 15x = -21

Combine like terms

6x = -21

Divide both sides by 6

6/6 x = -21/6

1x = -21/6

x = -7/2

x = -3.5 or -7/2

Plug this value into an equation to solve for y.

-3(-3.5) + y = 4

10.5 + y = 4

Subtract both sides by 10.5

10.5 - 10.5 + y = 4 - 10.5

y = -6.5

Check this answer by plugging the value of x into the other equation.

-9(-3.5) + 5y = -1

31.5 + 5y = -1

Subtract both sides by 31.5

31.5 - 31.5 + 5y = -1 - 31.5

5y = -32.5

Divide both sides by 5

y = -6.5 or -13/2

Therefore the solution is ( -3.5 , -6.5 )